Waste management practices and recycling intention among undergraduates students in higher learning institution / Siti Fahazarina Hazudin, Anis Barieyah Mat Bahari and Alia Ezrie Ashiqin Jamaludin - Siti Fahazarina, Hazudin; Anis Barieyah, Mat Bahari; Alia Ezrie Ashiqin, Jamaludin (2015)
The urgent implementation of solid waste management is crucial to be initiated corresponding to the current degree of environmental problems. Recycling practices is one of the well-recognized waste reduction strategies that can be employed at individual and institutional levels such as university to achieve a sustainable campus environment. The present study aims to investigate current waste management practices of University Teknologi MARA (Pahang) students and examine the factors that may influence intention of the students to involve in recycling behavior. A total of 150 out of 234 questionnaires were usable for analysis using Statistical Package for Social Science (SPSS, Version 20.0). The results showed that the most recyclable items produced by the students were papers (46%) along with other types of recyclable wastes such as bottles (17.3%), plastics (14%), books (11.3%), cans (10.7%) and others (0.7%). The study also revealed that about 77 percent of the respondents threw out the generated recyclable materials directly into rubbish bins as there was either no availability or lacking of recycling facilities around the campus. Further findings suggest that, only subjective norms have significant positive influence towards intention to recycle among the students. Both attitudes and perceived behavioral control were not statistically significant to influence the students‟ intention to perform recycling activities. We conclude that (1) the recycling program should be seriously conducted given that high amount of recyclable wastes have been produced by the students; (2) management of the university is advisable to conduct awareness talks on the importance of proper waste management and install necessary equipment and facilities for the convenience of recycling tasks; (3) the change agent (the students) also needs to be educated on the baseline recycling information on what and how to recycle to ensure a success implementation of campus recycling program.